Hubungan Kadar Karbon Monoksida (CO) dan Beberapa Faktor Risiko Tenaga Kerja dengan Tekanan Darah Juru Parkir Kawasan Malioboro - Yolamba Ervina SUjarwo; Heru Subaris Kasjono; Sri Muryani (Sanitasi: Jurnal Kesehatan Lingkungan, 2014)
Transportation is one of the biggest contributors to air pollution in the large urban of Indonesia, particularly from land transportation. Some people may be exposed to CO because of their work environment, and parking attendants are one of the most exposed group of workers to CO from main road. This study is aimed to investigate the relationship between levels of Carbon Mono-xide (CO) and several labor risk factors with blood pressure of parking attendants in Malioboro by conducting a cross sectional survey toward 64 respondents who were randomly selected. The results of this study were analyzed by using Pearson Product Moment, Spearman Rank Cor-relation, and Chi Square from SPSS. The statistical test results showed that relationships were found between the duration of work per week (p = 0,010 and p = 0,047) and work shift (p = 0,015 and p < 0,001) and systolic and diastolic blood pressure. The CO concentration, even though has correlation with diastolic blood pressure (p < 0,001), it has no relationship with the systolic one (p = 0,130). Meanwhile, for smoking habits, no relationship is found with both systolic and diastolic blood pressure (p = 0,05 and p = 0,911).